Genetic Characteristic of Javan Deer (Cervus timorensis de Blainville 1882), Babirusa (Babyrousa babyrussa) and Pig (Sus scrofa Linn) - Erna Suzanna (Department of Forest Resources Conservation and Ecotourism - IPB University, 1999)
Research on genetic polymorphism was conducted by using an clectrophoresis technique. Material used for this experiment consisted of 14 adult Javan deers (Cervus timorensis de Blainville, 1882), 8 babirusa (babyrousa babyrussa) and 5 adult pig (Sus scrofa, Linn) Electrophoretic result showed polymorphisms in plasm and red blood protein in these three kinds of animals. The highest average heterozygosity was 0.3555 0.1187 obtained in Babirusa, whereas pig and deer were 0.3033 0.0968 and 0.3176 0.1049 respectively. Genetic similarity between pairs of pig and babirusa was 0.73 and those of pig and deer was 1.83.